SOSIALISASI EDUKASI PASAR MODAL SEBAGAI UPAYA MENINGKATKAN LITERASI DAN MINAT INVESTASI SAHAM - La Ode Abdul Rakhman; Fariz Mustaqim (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This Community Service Program (PkM) aims to enhance students’ capital market literacy and interest in stock investment through capital market education and socialization activities. The implementation method adopts an educational and participatory approach conducted through material presentations, interactive discussions, and question-and-answer sessions covering basic concepts of the capital market, stock investment mechanisms, as well as investment risks and security aspects. The activity involved university students as the primary participants and was carried out in collaboration with the Capital Market Study Group (KSPM) and speakers from the Indonesia Stock Exchange. The results indicate an improvement in students’ understanding of the capital market and stock investment, reflected in better conceptual comprehension and more rational attitudes toward investing. In addition, students demonstrated increased interest, awareness, and confidence to learn about and gradually begin stock investment. Therefore, capital market education socialization has proven effective in improving capital market literacy and fostering students’ interest in stock investment.